(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The rapid development of information and communication technologies (ICT) in modern education requires new approaches to pedagogical practice. In particular, forming the information-constructive competence of future preschool educators has become a pressing issue. This article analyzes the process of developing educators’ professional competencies through pedagogical design technologies. It highlights the educational reforms underway in Uzbekistan, programs aimed at enhancing teachers’ digital competencies, and the role of innovative technologies. The study reveals the impact of pedagogical design on the professional preparation of future educators and offers methodological recommendations.